(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
The Julfa Formation in the Ali Bashi Mountains, northwest Iran, is very rich in brachiopods, particularly in its lower part, which has been dated by fusulinids and conodonts as Wuchiapingian in age. The brachiopod fauna described herein has been collected along the Main Valley section of the Ali Bashi Mountains, several hundred metres away from the historical sections described in the 1960’s and 1970’s. It comprises 39 species of the orders Productida, Orthotetida, Orthida, Rhynchonellida, Athyridida, Spiriferida, and Terebratulida, most of which are known in the coeval successions of Transcaucasia, Alborz Mountains in north Iran and in South China, confirming the Wuchiapingian age indicated by other proxies. A few of the brachiopod taxa range up into the Changhsingian Paratirolites Limestone. The shale and marly limestone at the base of the formation are dominated by semi-infaunal productids, that are progressively succeeded near the top of the lower part of the formation by a more diverse range of pedicle attached and cemented taxa, suggesting a shallowing upward trend and a shift to higher nutrient-substrates in more turbulent waters. The successive deepening trend recorded in the upper part of the Julfa Formation and in the overlying Ali Bashi Formation is very unfavourable for the brachiopods and only a few species survive, represented by small sized pediculate taxa that thrive on hardgrounds.